Resistance of cayenne pepper varieties (Capsicum frutescens) to anthracnose disease (Colletotrichum gloeosporioides) isolates from swampy areas - Ismed Setya Budi; Mariana Mariana; Amalia Fauziah (Universitas Lancang Kuning, 2023)
Anthracnose, a primary disease in chili plants caused by the pathogen fungus Colletotrichum sp., has proven significant losses by affecting harvests and inducing fruit decay. Control measures using synthetic pesticides have been implemented but yielded unsatisfactory results. The utilization of resistant varieties stands as a pertinent approach in early control efforts to minimize harvest losses. Additionally, the use of resistant varieties is a crucial component of integrated disease control implementation. This study aims to investigate the resistance levels of ten chili varieties commonly grown in swampy areas against specific isolates of Colletotrichum sp. present in swampy locations. The research, conducted in a randomized complete design in a greenhouse, tested ten varieties of cayenne pepper typically cultivated in swampy areas. The results revealed that the Hiyung variety is Susceptible, while Bara, Dewata 43 F1, Tiung Tanjung, Genie, Sekar, and CR-9 varieties exhibit moderate resistance. Conversely, Tiung Ulin, Alip, and Sret varieties are classified as resistant. The incubation period for tested cayenne pepper varieties varied, ranging from 3.5 to 5.3 days. A longer incubation period indicates greater resistance to anthracnose in chili varieties. The selection of resistant varieties is a pivotal step in anthracnose management, not only to minimize harvest losses but also to support an effective integrated control approach.